English Communication Strategies in Tourism - Sari, Angela Bayu Pertama (E-Journal of Tourism; Volume 5 Number 2 (September 2018), 2018)
The advance development in tourism industry is established through interrelated systems. One of which is the online booking platform. Not only for booking, but the online website also becomes the platform for giving reviews that portrays guests’ compliments or even complaints. Those compliments are powerful to give the guests positive image about the accommodation; however, the complaints will do in the contrary way. It may lead the accommodation into negative image. Accordingly, it is necessary for the accommodation providers to handle the complaints by giving the responses or reply of the guests’ reviews. That action will become the effort to turn the guests’ disappointment into satisfaction. In order to achieve it, several English communication strategies in handling complaints were executed. This research takes the responses of 8 accommodation providers towards the guests’ review as the subject of the research. It is conducted by using content analysis method. The results yields 4 strategies that exists in the responses, namely: attentiveness that correlates with the hospitality in communication appears 100% of the total responses; explanation that presents the clarification and elaboration appears in 79% of the total responses; effort, that is the presentation of the promising action in the future, exists in 46% of the total responses and the least is apology, that is the action of saying sorry, exists in 25% of the total responses.